frediandrikastrong@gmail. com - Kadek Frediandrika Adnantara (Jurnal Ilmiah Raad Kertha, 2021)
Supervision of any tourism activity; Prepare human resources that are reliable in their field, provide services to every tourism and provide security and comfort to tourists who visit Denpasar, to give the protection of the tour guide should have a license as to the problem how is the legal protection form given to tourists visiting Denpasar city? And how is the influence of tourist visits to Denpasar city towards the tourism investment climate?, this study uses the Emperis research type that is conducting field research with a Guan interview getting accountable data. The form of legal protection given to tourists visiting Denpasar, is through the authority of the police unit Pamong Praja in the enforcement of the regional regulation of Bali Province number 5 year 2016 about tour guide in Denpasar City is to conduct in each tourist attraction by working with related agencies namely prosecutors; Of justice Guide through Control coordination. Sidak/or sweeping Silakukan in accordance with the trust Perda number 5 year 2016. When a travel guide is found to be infringing, then it can be carried out in place and/or conducted investigation and investigation by PPNS until the proceeding, the other form of protection provides a sense of security and comfort to the tourists who visit the City of the tour guide in order to provide clear and strict information to the tourists both outside the attraction and while in the tourist attraction and the influence of tourists visit to Denpasar city against Tourism investment climate is able to contribute to the local revenue, open employment, improve accommodation and tourism investment, the development of tourism attraction in Denpasar city with a view of cultural tourism